2011
DOI: 10.1007/s10802-011-9531-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Control and Harsh Discipline as Predictors of Externalizing Problems in Young Children: A Comparative Study of U.S., Chinese, and Japanese Preschoolers

Abstract: We examined associations between child inhibitory control, harsh parental discipline and externalizing problems in 120 4 year-old boys and girls in the US, China, and Japan. Individual differences in children's inhibitory control abilities, assessed using behavioral tasks and maternal ratings, were related to child externalizing problems reported by mothers. As predicted, both child inhibitory control and maternal harsh discipline made significant contributions to child externalizing problems in all three coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 66 publications
2
55
1
1
Order By: Relevance
“…In numerous studies of developmental neurocognitive disorders it has been shown that poor inhibitory capacity is associated with general externalizing problem behaviors in both preschool and school-age children (Gagne et al 2011;Nigg et al 1999;Olson et al 2011). Young et al (2009) found poor inhibition to be more closely related to broadly defined externalizing problem behavior than were deficits in other executive function components, such as working memory updating and set shifting.…”
Section: Poor Inhibition and General Externalizing Problem Behaviorsmentioning
confidence: 99%
“…In numerous studies of developmental neurocognitive disorders it has been shown that poor inhibitory capacity is associated with general externalizing problem behaviors in both preschool and school-age children (Gagne et al 2011;Nigg et al 1999;Olson et al 2011). Young et al (2009) found poor inhibition to be more closely related to broadly defined externalizing problem behavior than were deficits in other executive function components, such as working memory updating and set shifting.…”
Section: Poor Inhibition and General Externalizing Problem Behaviorsmentioning
confidence: 99%
“…In particular, the EF skills of inhibitory control and response monitoring have been strongly implicated in externalizing problems (Olson et al, 2011; Bohlin et al, 2012) such as attention deficit hyperactivity disorder (ADHD; Barkley, 1997; Nigg, 2001; Shiels and Hawk, 2010). Although both externalizing issues and ADHD symptomology are prevalent among children experiencing prolonged psychosocial adversity (Juffer and van Ijzendoorn, 2005; Gunnar et al, 2007; Zeanah et al, 2009), it remains unclear whether differences in EFs may moderation risk for adaptive and maladaptive outcomes among children experiencing early adversity.…”
Section: Introductionmentioning
confidence: 99%
“…Erath, M. El-Sheikh, J. B. Hinnant, & E. M. Cummings, 2011; Olson et al, 2011). The association between maternal harshness and child behavior problems may reflect modeling of poor self-control, some aspect of temperamental risk transmission, or a combination of both.…”
Section: Introductionmentioning
confidence: 99%